TheoMedia : the Media of God and the Digital Age. - Byers, Andrew (The Lutterworth Press, 2014)
This book is a hermeneutical project in the church's wider efforts of trying to understand the technological mediascape of the twenty-first century. The purpose is not to offer a how-to guidebook to help churches incorporate communications technology into their worship and witness. Byers provides something more foundational, the beginnings of a way of constructing a theological frame of reference for understanding and appropriating media in the digital age and in the ages to come.
Keywords: Technology -- Religious aspects -- Christianity.; Digital communications -- Religious aspects -- Christianity.; Mass media -- Religious aspects -- Christianity.; Internet -- Religious aspects -- Christianity.; Technology -- Influence.; Digital communications -- Influence.; Mass media -- Influence.; Internet -- Influence.; Christianity and culture.; Internet -- Aspect religieux -- Christianisme.; Technologie -- Influence.; Transmission numérique -- Influence.; Médias -- Influence.; RELIGION -- Christian Ministry -- Missions.; RELIGION -- Christian Theology -- General.; Christianity and culture; Internet -- Religious aspects -- Christianity; Mass media -- Influence; Mass media -- Religious aspects -- Christianity; Technology -- Religious aspects -- Christianity